2019
DOI: 10.3168/jds.2018-15229
|View full text |Cite
|
Sign up to set email alerts
|

Positive relationships between body weight of dairy heifers and their first-lactation and accumulated three-parity lactation production

Abstract: describes the effect that BW of replacement heifers has on accumulated milk yields without discriminating whether the increased milk yield came from greater survival or from greater production per surviving cow. Further research on the relationships between BW and survival of heifers is required to confirm whether the heavier heifers survived longer than the lighter heifers, but could explain why the relationship between BW and 3-parity milk yields was more curvilinear than the relationship between BW and firs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
28
1
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(34 citation statements)
references
References 23 publications
3
28
1
2
Order By: Relevance
“…A previous study, based on the same heifers as the current study, showed that heifers that were heavier pre-breeding produced more milk in first lactation and accumulated over 3 parities, compared with heifers that were lighter (Handcock et al, 2019). Minimal studies have quantified the survival or reproductive benefits of heavier heifers.…”
Section: Introductionmentioning
confidence: 78%
See 2 more Smart Citations
“…A previous study, based on the same heifers as the current study, showed that heifers that were heavier pre-breeding produced more milk in first lactation and accumulated over 3 parities, compared with heifers that were lighter (Handcock et al, 2019). Minimal studies have quantified the survival or reproductive benefits of heavier heifers.…”
Section: Introductionmentioning
confidence: 78%
“…The range in 15-mo BW of FJ heifers where re-calving rate exceeded 70% was between 255 and 396 kg. The mean 15-mo BW of FJ heifers was 301.5 kg (Handcock et al, 2019), indicating a large range (141 kg) in 15-mo BW (46.5 kg below average and 94.5 kg above average) for which the first calving pattern was good.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…LW has also been found to be a reliable indicator of calf progress and, by proxy, allows producers to adjust management to improve productivity, 38 and future lactation performances. 43,44 Disease events cause losses in LW as it promotes energy diversion away from growth to immune defences, and diarrhoea causes nutrient loss, dehydration, and reduction in feed intake by suppressing appetite. 1,45 In this study, pneumonia was observed in 10 calves (IR = 23%, 95% CI = 13% to 37%), and diarrhoea was observed in eight animals (IR = 18%, 95% CI = 10% to 32%).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it has been demonstrated that calves heavier at birth and at weaning calved earlier than lighter calves [8]. Another study has reported a positive correlation between lifetime milk yield and BW of Holstein cows [9]. According to literature, the genetic selection pursued for decades has led to a progressive deterioration of fertility in Holsteins worldwide [10]; in fact productivity and overall fertility are genetically divergent traits.…”
Section: Introductionmentioning
confidence: 99%